PENGELOLAAN MANAJEMEN EKSTRAKULIKULER DI SDN 2 GUNEM MENINGKATKAN KETERAMPILAN HIDUP SISWA - Busyro, Muhammad Alvin; Widodo, Slamet (LPPM Universitas Bina Bangsa, 2024)
21st century life skills are very important to teach today's students. However, the reality in the field is that there are still many schools that have not taught 21st century life skills to their students. This is influenced by several factors, one of which is the lack of a forum provided by schools to students to improve life skills. Therefore, schools must take the time to accommodate students to improve life skills by means of extracurricular activities. This study aims to describe the management function of extracurricular activities at SDN 2 Gunem along with the supporting and inhibiting factors in the implementation of these activities. This research is a qualitative descriptive study with a case study as a research approach. Data was collected using in-depth interviews, documentation, and participatory observation methods. To maintain the validity of the data, this study used the techniques of extended participation, persistence / constancy of observation and triangulation. The findings in this study indicate the existence of an extracurricular activity program carried out by the school for one academic year, the existence of an organizational structure for each type of extracurricular activity, including the planning, mobilization or implementation process to the evaluation of extracurricular activities